O ensino de filosofia e o conceito de bildung (formação) em Nietzsche: um caminho para “tornar-se o que se é” - Matias, Pierre Wirom Pinheiro (2023)
This dissertation unfolds with the purpose of establishing an approach between the thoughts of the German philosopher Friedrich Nietzsche concerning education, specifically addressing the issue of formation, and the teaching of philosophy. The study aims to explore Nietzsche's considerations and criticisms of the educational system of his time, with its goals and objectives, in order to highlight points of interlocution with some current educational issues, especially regarding the reform of High School, which introduces the acquisition of knowledge and practices that can provide references and meanings for the construction of identity and life projects of young people and adolescents as a new competency. Thus, Nietzsche's ideas are taken as an instrument to reflect and argue in favor of a strategic proposal for teaching philosophy that articulates philosophical practices and knowledge with issues and problems arising from individual experience, emphasizing the specific formative contribution of education that comes from teaching and learning philosophy. Considering the flexibility of philosophical subjects and themes, the work focuses on a reflection about the construction of one's own identity in adolescence, as a personal issue and at the same time as an issue concerning all young people, which demands very specific and unique questions in their formative journey. As a methodology to implement philosophical work in the classroom that is coherent with the above, we propose the execution of a workshop of philosophy studies and practices based on Nietzsche's perspective of Bildung (Formation), in which the emphasis lies in the idea of formation as a process in which the individual seeks to "become what one is." This involves an educational task in which the presence of philosophical practice as an attitude of thought towards life and oneself constitutes a substantial element to foster the development of autonomy and freedom of thought and existence, a fundamental practice to stimulate the formation of an authentic character, shaped by the specificities and uniqueness of each individual. Regarding the adopted procedure, it specifically involves bibliographic research through an interpretative analysis/approach, with Nietzsche's theoretical framework as the guiding thread, allowing for the opening of new horizons and perspectives on the practices of teaching philosophy in the educational pedagogical environment.